Labour market returns to higher education in Vietnam - Tinh Doan (Kiel Institute for the World Economy (IfW), 2011)
This paper employs the Ordinary Least Squares, Instrumental Variables and Treatment Effect models to a new dataset from the Vietnam Household Living Standards Survey (VHLSS) to estimate return to the four-year university education in 2008. Our estimates reveal that the return to university education is about 17% (annualized) and robust to the various estimators. The return to higher education has significantly increased since the economic reform in late 1980s.
Keywords: C31; J31; O15; 330; economic transition; returns to higher education; IV model; Vietnam